(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2014)
In the present investigation, zooperiphyton communities comprised protozoa, rotifera copepoda, cladocera, ostracoda, conchostraca, insect’s larvae, oligochaeta, nematoda and mollusca. The group of zooperiphyton on three substrates showed no significant differences (P>0.05). Rotifers and protozoans were the most dominant group of total zooperiphyton abundance among three substrates. The interrelationships between zooperiphyton groups and physicochemical features of water as well as among different groups of zooperiphyton revealed that abundance and growth of zooperiphyton on substrates are influenced by water quality parameters and each with others. The ranges of physicochemical features of water of Dhanmondi lake were suitable for zooperiphyton communities including aquatic biota and also play a significant role to settle zooperiphyton on three substrates. That can help in enhancing productivity of the lake as well as sustaining aesthetic value of aquatic system. Asiat. Soc. Bangladesh, Sci. 40(2): 283-294, December 2014